ZAS: zakat application system for UiTM Tapah / Nurul Afizah Abd Aziz - Abd Aziz, Nurul Afizah (2021)
The goal of this project is to develop and install a web application system that will help students to apply zakat and staff to manage the zakat applications. Based on the problem statements that have been studied, it encourages this project to focus on solving the old system. In general, zakat application plays a significant role in the lives of university students. It gives students with financial difficulties hope. It can also allow ACIS employees to minimise workplace stress. Based on all of the observations, ZAS has the potential to outperform the present zakat application system. As a result, introducing a new system has the potential to improve the quality of zakat application.